Organoids with a Type 1 Collagen Scaffold to Model Bacterial Cancer Therapy - Lydia Farrell; Cleo Bonnet; Alethea Tang; Severina Peneva; Non G. Williams; Sunil Dolwani; Lee Parry; Paul Dyson (Cells)
Bacterial cancer therapy (BCT) is emerging as an important option for the treatment of solid tumours, with promising outcomes in preclinical trials. Further progress is hampered by an incomplete understanding of how oncotropic bacteria, such as attenuated strains of Salmonella enterica serovar Typhimurium, colonise tumours and the responses of both the bacteria and tumour cells to this colonisation. To model this, we developed organoids that are permissive for bacterial colonisation, replacing the conventional commercially available extracellular matrix (e.g., Matrigel) with a type I collagen matrix scaffold. A comparison of the two extracellular matrices indicated that type 1 collagen permitted an initial infection efficiency more than 5-times greater than with Matrigel. In addition, subsequent growth within type 1 collagen expanded bacterial cell numbers by over 10-fold within 4 days of infection. These organoids allow for the visualisation of bacterial chemoattraction, cell invasion and subsequent population of the interior lumen, and will permit the future optimisation of BCT. In addition, by establishing patient-derived organoids, we demonstrate a platform for developing future personalised treatments exploiting BCT.